LB1.5 The efficacy and safety of gentamicin for the treatment of genital, pharyngeal and rectal gonorrhoea: a randomised controlled trial. (8th July 2017) - Ross, Jonathan DC; Harding, Jan; Duley, Lelia; Montgomery, Alan A; Hepburn, Trish; Tan, Wei; Brittain, Clare; Meakin, Garry; Thandi, Sukhy; Lawrence, Tessa; Cole, Michelle; Wilson, Janet; et al.
Abstract : Introduction: Gentamicin is effective against N. gonorrhoeae in vitro and systematic reviews have reported cure rates of 62%–98% but the quality of studies was low and there are few data on pharyngeal or rectal infections. A recent large non comparative trial reported a cure rate of 100% when gentamicin was combined with 2g oral azithromycin, but a high incidence of gastrointestinal adverse effects limited tolerability and few extra-genital infections were included. The aim of this study was to evaluate the efficacy and safety of gentamicin versus ceftriaxone, each combined with 1g of azithromycin, for the treatment of gonorrhoea. Methods: A multi-centre, blinded, randomised controlled trial in participants with genital, pharyngeal or rectal gonorrhoea who received either gentamicin 240 mg or ceftriaxone 500 mg (each as a single intramuscular injection). The diagnosis of gonorrhoea was based on a positive nucleic acid amplification test (NAAT) or gram stained smear on microscopy. The primary endpoint was microbiological cure based on NAAT two weeks after treatment. The trial had 90% power to detect non-inferiority with a lower CI for an absolute risk difference of 5%. Data collection was completed in March 2017. Results: 720 patients from 14 sexual health clinics in England were randomised to receive ceftriaxone (n=362) or gentamicin (n=358). Baseline characteristics of the two groups were well balanced. 306 participants randomised to ceftriaxone (85%) and 292 randomised to gentamicin (82%) had primary outcome data available. 98% (299/306) and 91% (267/292) of participants randomised respectively had clearance of gonorrhoea at 2 weeks – adjusted risk difference −6.4% (95% CI −10.4%, −2.4%). Pre-specified sensitivity analyses supported this result. Clearance at the genital site was 98% and 94%, at pharynx 96% and 80% and at rectum 98% and 90%. The frequency of side effects was similar between treatment groups. Conclusion: Gentamicin is not non-inferior to ceftriaxone for the treatment of gonorrhoea.